Residential instability, running away, and juvenile detention characterizes commercially sexually exploited youth involved in Washington State's child welfare system. (April 2020) - Pullmann, Michael D.; Roberts, Norene; Parker, Elizabeth M.; Mangiaracina, Kelly J.; Briner, Leslie; Silverman, Morgan; Becker, Jeremy R.
Abstract: Background: Federal policy in 2015 expanded the definition of "child abuse" to include human trafficking. As a result, child welfare agencies are newly responsible for identifying and providing services for youth in state care who are or at-risk of commercial sexual exploitation. Objective: To describe the demographics, state-dependent living situations, and juvenile detention usage of state-dependent commercially sexually exploited youth. Participants and setting: Eighty-three state-dependent youth (89.2 % female, mean age at identification = 15.5 years, SD = 1.5, Range = 11.7–19.1 years) who were confirmed or strongly suspected of commercial sexual exploitation. Methods: Secondary analysis of lifetime administrative record data from child welfare and juvenile justice systems using descriptive statistics. Results: Youth experienced early and frequent contact with the child welfare system. Youth experienced an average of 27 living situation disruptions while in the care of child welfare, with a disruption an average of every 71 days, primarily due to running away. Nearly 9 out of 10 youth had at least one runaway episode, and for these youth, there were an average of 8.6 runaway episodes. Three out of four youth had at least one juvenile detention episode, and for these youth, the average number of detention episodes was 9.2. Conclusions: We provide the context of a cycle of multisystem entanglement, whereby running away may be both a response to and cause of further system involvement and commercial sexual exploitation, and call for evidence-based interventions focused on reducing running away for these youth.